(untitled) (Eurasian Medical Research Periodical, 2023)
The results of the study of the initial autonomic status and autonomic regulation in patients with bronchial asthma are presented. The study involved 102 children aged 12 to 18 years in the phase of exacerbation of the disease. Vegetative status with moderate severity of the disease was characterized by sympathicotonia, high vegetative reactivity of the hypersympathic-tonic type. In adolescents with a severe course of bronchial asthma, there is a pronounced imbalance of autonomic regulation, characterized by a decrease in the tone of the sympathetic section at rest, an asymptomatic variant of the response to orthostatic load.